2002
DOI: 10.1002/eqe.174
|View full text |Cite
|
Sign up to set email alerts
|

A recursive decomposition algorithm for network seismic reliability evaluation

Abstract: SUMMARYA new probabilistic analytical approach to evaluate seismic system reliability of large lifeline systems is presented in this paper. The algorithm takes the shortest path from the source to the terminal of a node weight or edge weight network as decomposition policy, using the Boolean laws of set operation and probabilistic operation principal, a recursive decomposition process then could be constructed. For a general weight network, the modiÿed Torrieri method (NTR=T method) is introduced to combine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 14 publications
0
58
0
Order By: Relevance
“…1 is, the less is its contribution to the connectivity of the system. It is illustrated in functions (5) and (8). The recursive decomposition algorithm prioritizes solving for the shortest road and the shortest cut set.…”
Section: The Algorithm Structure Of the Complex Network Connectivitymentioning
confidence: 99%
“…1 is, the less is its contribution to the connectivity of the system. It is illustrated in functions (5) and (8). The recursive decomposition algorithm prioritizes solving for the shortest road and the shortest cut set.…”
Section: The Algorithm Structure Of the Complex Network Connectivitymentioning
confidence: 99%
“…However, for the node weighted network and general weighted network, the proposed algorithm can also be used after some small changes are made. A detailed process was illustrated by Li and He (2002).…”
Section: Structure Function and Related Theoremsmentioning
confidence: 99%
“…Also, Yoo and Deo (1988) compared four current algorithms and concluded that Dotson's algorithm was the most effi cient. Introducing the concept of "system structure function" and combining Dotson's algorithm with computer storage, Li and He (2002) presented a recursive decomposition algorithm, in which the probabilistic inequality is used to control the computation time and ensure the error bound remained within the predefi ned scope. This algorithm provides an effi cient approach for large network reliability evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…where j = 1− j means the complement of j, which is viewed as a Boolean variable in the RDA [5]. It is clear from the above definition that the larger I prob, ji means a larger influence of edge j on node i.…”
Section: Introductionmentioning
confidence: 98%
“…where P Si is the seismic reliability of node i, M is the number of all disjoint minimal paths between the source and node i, L il is a disjoint minimal path between the source and node i, which can be obtained using the RDA [5]; *P{L il }/* p j can be expressed as…”
Section: Introductionmentioning
confidence: 99%